In Vivo Femtosecond Laser Subsurface Cortical Microtransections Attenuate Acute Rat Focal Seizures. (6th September 2018) - Nagappan, Shivathmihai; Liu, Lena; Fetcho, Robert; Nguyen, John; Nishimura, Nozomi; Radwanski, Ryan E; Lieberman, Seth; Baird-Daniel, Eliza; Ma, Hongtao; Zhao, Mingrui; Schaffer, Chris B; Schwartz, Theodore H
Abstract: Recent evidence shows that seizures propagate primarily through supragranular cortical layers. To selectively modify these circuits, we developed a new technique using tightly focused, femtosecond infrared laser pulses to make as small as ~100 µm-wide subsurface cortical incisions surrounding an epileptic focus. We use this "laser scalpel" to produce subsurface cortical incisions selectively to supragranular layers surrounding an epileptic focus in an acute rodent seizure model. Compared with sham animals, these microtransections completely blocked seizure initiation and propagation in 1/3 of all animals. In the remaining animals, seizure frequency was reduced by 2/3 and seizure propagation reduced by 1/3. In those seizures that still propagated, it was delayed and reduced in amplitude. When the recording electrode was inside the partially isolated cube and the seizure focus was on the outside, the results were even more striking. In spite of these microtransections, somatosensory responses to tail stimulation were maintained but with reduced amplitude. Our data show that just a single enclosing wall of laser cuts limited to supragranular layers led to a significant reduction in seizure initiation and propagation with preserved cortical function. Modification of this concept may be a useful treatment for human epilepsy.